Agent-based modeling and simulation of blood vessels in the cardiovascular system. (April 2019) - Bora, Şebnem; Evren, Vedat; Emek, Sevcan; Çakırlar, Ibrahim
The purpose of this study is to develop a model to simulate the behavior of the human cardiovascular system for use in medical education. The proposed model ensures that the output of the system is accurately represented in both equilibrium conditions and imbalance conditions including in the presence of adaptive agents. In this study, field experts develop an agent-based blood vessel model, i.e., a submodel for the stated purpose. In the proposed blood vessel model, vessels are represented by agents whereas blood flow is represented by the interaction between agents. Adaptive behavior shown by vessels in terms of resistance to the blood flow is defined by the agents' properties, which are used as the basis for calculating and graphically representing the physical parameters of blood flow, specifically blood pressure, blood flow velocity, and the resistance of the vessel. The adaptation of the vessel agents is supported by a case study, which demonstrates the adaptive behavior of the blood vessel agents through a negative feedback control mechanism. The blood vessel model proposed is flexible in nature such that it can be adapted to account for the behavior of the vessel sections in any vascular structure.